An insight into gut microbiota and metabolites in the mice with adenomyosis - Chen, Peipei; Wang, Kun; Zhuang, Mingyan; Fu, Xianyun; Liu, Shidan; Chen, Minmin; Lei, Ya (Frontiers in Cellular and Infection Microbiology, 2023)
Background Adenomyosis (AM) is a benign uterine disease characterized pathologically by the invasion of endometrial tissue into the myometrium. The pathogenesis of AM is still far from clear. Although the gut microbiome and metabolomics are thought to contribute to a variety of diseases, the role of them in AM has not been revealed. Objective To investigate changes in the gut microbiota and derived metabolites in AM mice. Method Female ICR mice were randomly assigned to AM and control groups, and pituitary transplantation was employed to perform AM modeling. Then, the fecal samples were obtained for microbial (16S rRNA gene sequencing) and metabolomic (liquid chromatography mass spectrometry, LC-MS) analysis. Result The results of gut microbiota analysis showed that the intestinal microbiota composition of AM mice was altered. The ratio of Firmicutes/Bacteroidetes and the abundance of Lactobacillus in AM group increased compared with the control group. Sixty differential expressed metabolites were identified in intestinal metabolites, mainly involved in steroid hormone biosynthesis, cysteine metabolism, and glutamate metabolism. Further, correlation analysis verified that there was a relationship between gut microbiota and metabolites in AM mice. Conclusion The unique gut microbiota and metabolites in AM mice interact with each other, which may play a role in the process of AM.